Savings in Central Eastern Europe - Mechthild Schrooten; Sabine Stephan (Deutsches Institut für Wirtschaftsforschung (DIW), 2001)
The paper seeks to add to the existing literature on aggregate and private savings by focusing on transition economies. We use panel data over the period 1989-1998 and estimate a fixed-effects model. In Central Eastern European Countries, aggregate and private savings are driven by almost the same forces – this is the central focus of the paper. The most important factor behind both types of saving is income. Furthermore, it is shown that domestic saving and foreign capital are not operating as substitutes. This is an indicator for the rudimentary integration into the international financial market.
Keywords: G2; E21; 330; Savings; transformation; panel data; Sparen; Einkommenshypothese; Übergangswirtschaft; Schätzung; Osteuropa